2015
DOI: 10.18869/acadpub.jnms.2.4.37
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of professional autonomy and the association with individual factors among nurses in the Southeast of Iran

Abstract: Background and Purpose: Professional autonomy in nursing is defined as working in a self-determined environment and making decisions based on professional judgment. This study aimed to evaluate professional autonomy and its association with individual factors in nurses employed at teaching hospitals affiliated to Kerman University of Medical Sciences in the southeast of Iran in 2013. Methods: This was a descriptive analytical study, and required data were collected by quota sampling using self-administered que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
4
12
0
Order By: Relevance
“…Findings indicated that nurses who attained higher education tended to have a greater degree of professional autonomy in their jobs. This finding supports previous studies (Cajulis et al, 2007;Ericsson, Whyte, & Ward, 2007;Motamed-Jahromi et al, 2015;Mrayyan, 2005). (Mrayyan, 2005).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Findings indicated that nurses who attained higher education tended to have a greater degree of professional autonomy in their jobs. This finding supports previous studies (Cajulis et al, 2007;Ericsson, Whyte, & Ward, 2007;Motamed-Jahromi et al, 2015;Mrayyan, 2005). (Mrayyan, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…Findings indicated that nurses who attained higher education tended to have a greater degree of professional autonomy in their jobs. This finding supports previous studies (Cajulis et al, ; Ericsson, Whyte, & Ward, ; Motamed‐Jahromi et al, ; Mrayyan, ). For instance, Cajulis et al, reported higher professional autonomy in nurses who were masters—prepared as compared with nurses with bachelor's degree.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Autonomy appears to be linked to the authority to make decisions, and the freedom to make clinical judgements, choices and actions related to patients and families (Skår, 2009). The ability of care staff to autonomously make judgements or decisions in care is shaped by knowledge and experience (Motamed‐Jahromi et al, 2015; Tanner, 2006). Therefore, possible reasons for the emergence of this subscale could be that participants had little knowledge about PCC, had little practical experience with PCC or did not have Japanese national qualifications as nurses or care workers.…”
Section: Discussionmentioning
confidence: 99%